Subperiosteal abscesses as a complication of Acute Mastoiditis in pediatric age: 22-year experience - Chantre, Tiago (2022)
Objectives: Comparison of the surgical results of patients submitted to Subperiosteal Abscess (SS) drainage compared to those submitted to mastoidectomy. Study design: Observational and retrospective. Material and Methods: Review of clinical records of pediatric patients diagnosed with SA (n=56). Results: The incidence of AS has remained constant, with an average of 2.5 cases/year. SA drainage with myringotomy was the surgical approach chosen in 43 patients (77%), while 6 underwent mastoidectomy (11%) and 7 underwent drainage and mastoidectomy (13%). The only statistically significant difference between groups was the mean length of hospital stay, which was longer in the mastoidectomy group. Conclusions: SA drainage combined with intravenous antibiotic therapy is an effective first-line treatment for SA in pediatric age. No higher risk of complications was found in the group of patients treated with drainage compared to the group undergoing mastoidectomy.